2009
DOI: 10.1007/s10562-009-9922-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preparation Parameters of MCM-41 Supported Pt/Ni Catalysts and their Hydrogenation Properties

Abstract: A series of Pt 50 Ni 50 supported on MCM-41 catalysts were prepared via wet co-impregnation of the metal salts H 2 PtCl 6 and NiSO 4 Á6H 2 O. The metal salts were reduced using NaBH 4 and catalytic activities of the catalysts were investigated for the hydrogenation of benzene to cyclohexane. The effect of various reduction conditions such as reduction temperature, NaBH 4 concentration and the medium in which reduction was carried out was investigated. Results show that optimum catalytic activity occurs when ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Bimetallic catalysts have been utilized in many reactions such as hydrogenation, dehydrogenation, and reforming due to their unique properties that are distinctly different from those of the corresponding monometallic catalysts. [1][2][3][4][5][6][7] Many experimental and theoretical studies have been performed to determine the activity and stability of bimetallic systems on well-defined single crystal surfaces. 4,8,9 It has been demonstrated that the structural and electronic properties of bimetallic surfaces strongly affect catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic catalysts have been utilized in many reactions such as hydrogenation, dehydrogenation, and reforming due to their unique properties that are distinctly different from those of the corresponding monometallic catalysts. [1][2][3][4][5][6][7] Many experimental and theoretical studies have been performed to determine the activity and stability of bimetallic systems on well-defined single crystal surfaces. 4,8,9 It has been demonstrated that the structural and electronic properties of bimetallic surfaces strongly affect catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Surface functionalization of MCM-41 also helps for quantitative and high dispersion of Pt nanoparticles. Up to now, siliceous MCM-41 [32], Ti-MCM-41 [33], Al-MCM-41 [29], Fe-MCM-41 [34], V-MCM-41 [35], other metalloaded MCM-41 [36] and amine-functionalized MCM-41 materials [37] have been used as supported materials for high dispersion of Pt nanoparticles. Moreover, bimetallic nanoparticles supported on amine-functionalized MCM-41 and Al-MCM-41 were also used for isomerization and hydrocracking of n-decane [38,39].…”
Section: Hexagonal Mesoporous Silica Molecular Sievesmentioning
confidence: 99%